Associations of Alcohol Consumption, Sexual Assault History, Severity, and Revictimization With College Women's Bystander Behaviors in Alcohol-involved Settings. Issue 23 (December 2021) - Marcantonio, Tiffany L.; Willis, Malachi; Schisler, Eric D.
Sexual assault victimization (SAV) histories may impede, increase, or have no effect on women's risk recognition. Yet, even though risk recognition is a component of bystander intervention, the effect of SAV on bystander behaviors is understudied. For example, how different SAV histories, such as the severity of the assault and if women were revictimized since entering college, have not been examined with bystander behaviors; we intended to address this gap in the literature. Building on recent work, we also examined the potential interactive effects of alcohol consumption and SAV history in predicting bystander behaviors. College women ( n = 560) completed a web-based survey on alcohol consumption, SAV experiences since entering college, and bystander behaviors in alcohol-involved settings. We found that the effect of SAV history on bystander behavior varied based on alcohol consumption. As women's alcohol consumption increased so did their self-reported engagement in bystander behaviors. For non-victims, increased alcohol consumption had a greater positive effect on their bystander behaviors than victims. However, after a certain quantity of alcohol was consumed, both victims and non-victims reported decreased bystander behavior. Finally, alcohol consumption did not interact with severity of SAV or revictimization status in predicting bystander behavior. Findings suggest alcohol consumption may be more influential on bystander behaviors for women with no history of SAV; however, consuming a greater quantity of alcohol is related to a decrease in bystander behavior—regardless of SAV history. Given these findings, more work is needed to explore when and how alcohol impedes, and potentially encourages, bystander behavior. How SAV histories relate to bystander behaviors also warrants further research.